Investigation of Enceladus plume composition, and the possibility of a sample return mission - Klasson, Martin (2009)
The discovery of Enceladus geologically active south pole by the Cassini spacecraft 2005 shifted focus to this small icy moon of Saturn. Methane and other hydrocarbons were detected in the plume emerging from Enceladus south pole, extending thousands of kilometers into space. Scientists have discussed whether this methane might have biotic or abiotic sources. This thesis work aims to produce results for further understanding of Enceladus interior. The work described here aims at simulating the methane production responsible for the methane in the plume. This will be done by experimental simulations of thermogenic methane production, Fischer-Tropsch synthesis and the growth of methanogenic organisms in simulated Enceladus conditions. The results of these experiments will then be compared to those gained by the Cassini spacecraft, and the conclusion of the comparison in favor of the abiotic thermogenic methane production being responsible for the methane in the plume and also other hydrocarbons detected. This thesis work will also investigate the energy cost to send a spacecraft to take samples of Enceladus plume and bring these back to Earth. The mission time would be very long, 12.2 years, when the minimum velocity change (DV) of the spacecraft is used, so we will also calculate the DV cost when the mission time is halved. This cost was more than double of the lowest. Validerat; 20101217 (root)